Grouping by date/time - Griffiths, Dawn (O'Reilly Media, Inc., 2024)
PivotTables, one of Excel's most powerful features, let you interactively analyze, summarize, and explore large amounts of data with just a few mouse clicks. You can slice and dice data in many different ways, apply different summaries, and insert custom calculations to go beyond Excel's built-in aggregations. This collection of Shortcuts helps you get the most out of PivotTables, quickly and easily.
Keywords: Microsoft Excel (Computer file) -- Handbooks, manuals, etc; Electronic spreadsheets; Business -- Computer programs; Tableurs